STUDY OF SOME FACTORS INFLUENCING BIRTH WEIGHT OF ARBIA GOATS IN GUELMA DISTRICT, ALGERIA - A. Boumezaouet; R. Zebsa; L Mebirouk-Boudechiche (Journal of Animal and Plant Sciences, 2023)
Arbia goat is the most common indigenous breed of North-eastern Algeria, and it has an acceptable production capacity in that region. The gender, litter size, parity, year and month of kidding were used as source of variation of birth weight. A total of 474 kids, reared by nine smallholders under extensive breeding conditions,, were weighed immediately after birth during two seasons of kidding. A Linear mixed effects model (in R software) was used to analyse our results and revealed that average birth weight was 2.63±0.31 Kg with a significance difference between sex (2.69 ±0.32 Kg and 2.60 ±0.30 Kg for males and females, respectively) (P≤0, 0001). Kids born as single were heavier (2.91 ±0.34 Kg) than those born as twins and triplets (2.61 ±0.26 Kg and 2.33 ±0.27 Kg, respectively) (P≤0,0001). A positive relationship between age of dam and birth weight was found (P≤0.01). Month of birth has a significant effect on birth weight. Synchronization of kidding during November and December is desired.
Keywords: Algerian native goats; birth weight; extensive system; parity; sex; type of birth